2019
DOI: 10.1111/jgs.16216
|View full text |Cite
|
Sign up to set email alerts
|

Does Physician Retirement Affect Patients? A Systematic Review

Abstract: OBJECTIVES Older patients that have aged with their doctors will likely experience their physician retiring. It is unclear if this interruption in continuity of care leaves patients at risk for adverse events or whether a new physician improves care. We sought to identify and synthesize findings from all articles examining the association between physician retirement and patient outcomes. DESIGN Systematic review. We searched English‐language articles cataloged in Medline, Embase, Cochrane, and PsycINFO, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…More time might be needed to establish a trusting relationship enabling patients to feel comfortable and disclose more information. Indeed, despite replacement, physician retirement was found to be associated with unfavourable outcomes such as with the loss of a trusted advisor, with difficulty with transition or with emotional distress (Lam et al., 2020). Further research is needed to clarify the existence of these three empathic processes.…”
Section: Discussionmentioning
confidence: 99%
“…More time might be needed to establish a trusting relationship enabling patients to feel comfortable and disclose more information. Indeed, despite replacement, physician retirement was found to be associated with unfavourable outcomes such as with the loss of a trusted advisor, with difficulty with transition or with emotional distress (Lam et al., 2020). Further research is needed to clarify the existence of these three empathic processes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review assessed how physician Open access retirement impacted patients and found mainly unfavourable outcomes, mainly published as anecdotes and qualitative studies. 2 The authors point to some possible mechanisms related to difficulty accessing care, difficulty with transition and poor handover of information. Our results indicate that special attention should be given to elderly and frail patient groups as early as possible when the discontinuity is known to happen.…”
Section: Comparisons With Existing Literaturementioning
confidence: 99%
“…Loosing access to your general practitioner (GP) can be emotionally stressful, 1 and patients can be vulnerable during the transition of care from one GP to another. 2 Some discontinuities of GP practice are inevitable, as GPs retire, get sick and take parental leave. A study on American patients forced to change their physician due to healthcare insurance changes, indicated this disruption to be damaging to the patient receipt of quality GP care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are longstanding concerns about the potential impact of primary care physician retirements on patient access to and continuity of care, and on service supply more broadly [ 1 – 8 ]. While considerable research has been done on the services that older physicians provide as they age and transition out of the workforce [ 1 , 2 , 9 – 13 ], very little attention has been given to how physician retirement affects patients [ 7 ]. Existing work suggests that disruption to longitudinal relationships between patients and physicians has been associated with difficulty accessing care [ 14 ], emotional distress [ 14 , 15 ], poorer health outcomes [ 8 ], and decreased use of downstream primary care services [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%